A maldição das palavras e o sujeito dilacerado de Marcelo Mirisola (2009) - Scheel, Marcio [UNESP] (My University, 2010)
There is an area in the Brazilian Contemporary Literature which is articulated according to the first person narrator who presents the problematic of the own creational action, the expression of a conflictual subjectivity divided between the vertiginous dive into itself – what would imply in a renounce of the world and the reality, where the authors’ work are their only matter – and the social participation - not as an awareness, but as the recognition of the limits and impasses which the real representation imposes on the creative writing. Therefore, this article proposes a reading on the novel O Azul do Filho Morto (2002) by Marcelo Mirisola, to try to situate him into the recent Brazilian literary production, as well as to reflect on his narrative the complex notion of authorship which is called into question on his novels, since they produce an intrincate imbrication between the fictional subject and the empirical image of the writer himself, breaking and confusing the limits between the fictional discourse and the extralinguistic reality which is evoked, manipulated, distorted and made unstable on his representational process.

Há uma vertente da literatura contemporânea brasileira que se articula em função de narradores em primeira pessoa que colocam em jogo a problemática do próprio gesto criador, da expressão de uma subjetividade conflitiva, cindida entre o mergulho vertiginoso em si mesma – o que implicaria em uma renúncia ao mundo e ao real, fazendo da obra sua única matéria – e a participação social, não como tomada de consciência, mas como o reconhecimento dos limites e impasses que a representação do real impõe à escritura. Nesse sentido, o presente artigo propõe uma leitura do romance O Azul do Filho Morto (2002), de Marcelo Mirisola, procurando situá-lo no interior da recente produção literária brasileira, bem como pensar sua narrativa a partir da complexa noção de autoria que seu romance põe em circulação, já que este produz uma intrincada imbricação entre o sujeito ficcional e a imagem empírica do próprio escritor, rompendo e confundindo os limites entre o discurso da ficção e a realidade extralinguística que ele evoca, manipula, distorce e instabiliza no processo representacional.
Keywords: Autor; Ficção; Real; Representação; Romance; Sociedade; Author; Fiction; Novel; Real; Representation; Society